Human complement regulators C4b-binding protein and C1 esterase inhibitor interact with a novel outer surface protein of Borrelia recurrentis - Grosskinsky, Sonja; Schott, Melanie; Brenner, Christiane; Cutler, Sally J.; Simon, Markus M.; Wallich, Reinhard (PLoS neglected tropical diseases, 2010)
The spirochete Borrelia recurrentis is the causal agent of louse-borne relapsing fever and is transmitted to humans by the infected body louse Pediculus humanus. We have recently demonstrated that the B. recurrentis surface receptor, HcpA, specifically binds factor H, the regulator of the alternative pathway of complement activation, thereby inhibiting complement mediated bacteriolysis. Here, we show that B. recurrentis spirochetes express another potential outer membrane lipoprotein, termed CihC, and acquire C4b-binding protein (C4bp) and human C1 esterase inhibitor (C1-Inh), the major inhibitors of the classical and lectin pathway of complement activation. A highly homologous receptor for C4bp was also found in the African tick-borne relapsing fever spirochete B. duttonii. Upon its binding to B. recurrentis or recombinant CihC, C4bp retains its functional potential, i.e. facilitating the factor I-mediated degradation of C4b. The additional finding that ectopic expression of CihC in serum sensitive B. burgdorferi significantly increased spirochetal resistance against human complement suggests this receptor to substantially contribute, together with other known strategies, to immune evasion of B. recurrentis.
Gesehen am 07.06.2021